Gaya Pengajaran Generasi X dan Y dalam Perspektif Motivasi Belajar Mahasiswa - Christien Adriani Karambut; Jacob Tateol Silangen Makapedua; Margaretha Anatje Rundengan; Nisba Silvana (Universitas Merdeka Madiun, 2026)
This study aims to analyze Generation Z students' perceptions of Generation X and Y lecturers' teaching styles, and to identify student learning motivation levels in a vocational higher education context. Conducted at the Campus X with 210 respondents using census sampling, data were collected via a 1–5 Likert scale questionnaire and analyzed through descriptive statistics. Findings reveal that lecturers' ability to contextualize course material with real-world work scenarios received the highest appreciation (mean 4.2), while experiential learning activities such as industry visits and guest speakers scored lowest (mean 2.6). Basic technology integration in teaching remained at a moderate level (mean 3.0), indicating that Generation X and Y lecturers are still in a transitional phase of digital adoption. Student learning motivation averaged 3.5 overall, with achievement-based motivation as the most dominant dimension (mean 3.6), while overall learning enjoyment recorded the lowest score (mean 3.2). These findings highlight the urgency of a pedagogical transformation that synergistically integrates active learning, digital technology, and industry-based experiential learning to enhance Generation Z students' learning motivation.